Phylogeny of the subfamily Streblinae (Diptera: Streblidae) and historical host-parasite association - Alcantara, Daniel Maximo Corrêa de (2020)
The paradigm upon which much of the theoretical and empirical framework was based for the study of historical associations has not been able to accommodate the available evidence. These inconsistencies enabled the emergence of the \"Stockholm Paradigm\". There are different groups that have potential to be a model system for studying historical associations, such as Streblidae. The family is characterized as a highly specialized group of flies that are ectoparasitic on bats, feeding on the blood of their hosts. The association between species of Streblidae and their hosts may be a good model system to understand the host-parasite relationship under the Stockholm Paradigm. However, reconstructing a relationship hypothesis is crucial before starting a study of the historical association. To study the relationship within Streblidae and the host-parasite associations, the thesis was divided into two main parts. In chapter 2, we present the most comprehensive molecular phylogeny of New World Streblidae to date, including a fossil-calibrated estimates of divergence dates. Our analysis supports the monophyly of New World Streblidae, Nycterophiliinae and Streblinae, but a non-monophyletic Trichobiinae. Our estimates suggest that New World Streblidae arose at Lower Miocene. Host-switch is recovered as the main event in the associations between species of Streblidae and their hosts. We suggest roost ecology as an important mechanism in the association between species of Streblidae and their hosts. In chapter 3, the phylogeny of the subfamily Streblinae is presented based on morphological characters. We sampled all valid species of Streblinae. Results strongly support the monophyly of Streblinae, with Anastrebla, Metelasmus and Paraeuctenodes also as monophyletic. In turn, Strebla is recovered as paraphyletic in relation to Metelasmus. We present a historical overview on the delimitation of Streblinae, and discuss the importance of a new interpretation of the characters